Development of an instrument to measure the cultural competence of health care workers - Pedrero, Victor; Bernales, Margarita; Chepo, Macarena; Manzi, Jorge; Pérez, Miguel; Fernández, Paulina (Revista de Saúde Pública, 2020)
OBJECTIVE: To validate an instrument measuring the cultural competence in health care workers from Chile. METHODS: Using Sue & Sue’s theoretical model of cultural competence, we designed a scale, which was assessed by health care workers and experts. Subsequently, the scale was applied to a sample of 483 different health care workers, during 2018 in Santiago de Chile. The analysis included: exploratory and confirmatory factor analysis, estimation of reliability, and analysis of measurement bias. Finally, the level of cultural competence was calculated for every professional who participated in this study. RESULTS: The final scale include 14 items that are grouped into three dimensions concordant with the theoretical model: sensitivity to own prejudices, cultural knowledge, and skills to work in culturally diverse environments. This scale showed good fit in factor models, adequate reliability and lack of evidence of measurement bias. Regarding the performance of health care workers, sensitivity showed a lower level compared with the other dimensions evaluated. CONCLUSION: The scale for measuring the level of cultural competence in health care workers (EMCC-14) is a reliable instrument, with initial support for its validity, which can be used in the Chilean context. Additionally, the results of this study could guide some possible interventions in the health sector to strengthen the level of cultural competence.